Óleos essenciais da família Lamiaceae utilizados para controle de culicídeos vetores: uma revisão sistemática - Santos, Aytana Vasconcelos dos (2022)
As the diseases spread by mosquitoes vector grow significantly in recent times, this represents a serious epidemic to society, aggravating existing public health problems, causing problems. Thus, in the search for natural alternatives, many studies have highlighted the use of essential oils obtained from the Lamiaceae family. Thus, the objective of this work was to carry out a systematic review on the use of essential oils from species of the Lamiaceae family that have larvicidal properties against vectors (Aedes, Anopheles and Culex). It was developed and described in accordance with the Preferred Reporting Items for Systematic Reviews and MetaAnalyzes (PRISMA) guidelines. Thus, electronic database searches (Embase, Scopus, PubMed and ScienceDirect), an overview of additional sources. After the initial search, 398 articles were obtained for complete Reading. From these, 78 full original articles were included. It was observed that most of the studies used as parts of aerial plants for maintenance of EO. The most frequently reported genus was Ocimum. The essential oils were extracted through hydrodistillation combined with GC/MS, the lethal concentration (LC50) of acute toxicity responsible for larval mortality was also reported, and thus, it was found that the most active essential oils are rich in sesquiterpenic hydrocarbons, oxygenated sesquiterpenes and monoterpene hydrocarbons. About 70% of the essential oils extracted had moderate mortality. This review presents that essential oils can be used in the control of arboviruses, however, it is suggested that further studies may be conducted on safety and formulations for field application of essential oils.